Hubungan Tingkat Pengetahuan dengan Perilaku Personal Hygiene saat Menstruasi pada Remaja Putri SMP Negeri 1 Surakarta - SUTRISNO, Sutrisno (Sahabat Publikasi Kuu, 2025)
Introduction : Menstrual hygiene is an important aspect of health for adolescent girls. However, many face challenges in maintaining proper hygiene during menstruation. In Indonesia, most young women show poor personal hygiene practices, which can cause health problems. Purpose : To determine the relationship between the level of knowledge and personal hygiene behavior during menstruation in young women at SMP Negeri 1 Surakarta. Method : This research is a type of correlative descriptive research with a cross sectional design. The sampling technique used proportional random sampling with 70 respondents. The research instrument uses a questionnaire and the data analysis technique uses the Gamma statistical test. Result : The results of the analysis showed that 32 (45.7%) respondents had sufficient knowledge about personal hygiene and 33 (47.1%) respondents had adequate personal hygiene behavior. The results of the Gamma statistical test obtained a P-value = 0.001 (P -value<0.05) with a correlation value of 0.812. Conclusion : There is a significant and strong relationship between knowledge and personal hygiene behavior during menstruation in young women at SMP Negeri 1 Surakarta.